2021
DOI: 10.18371/fcaptp.v4i35.222015
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting the Risk of Money Laundering Through Financial Intermediaries

Abstract: The increase in international trade, the active development of integration and convergence processes in the global financial market, the rapid implementation of digital technologies in various spheres of life, as well as the growth of cross-border organized crime have led to increased shadow economic activity and improved forms and methods of money laundering. Under these conditions, it is essential to assess the risk of money laundering adequately through financial institutions and determine its dynamics in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The problems of the rapid economic crisis aggravation in Ukraine and the world, the shortage of financial resources, the bankruptcy of a significant number of companies, which only worsened in the conditions of the COVID-19 pandemic, and in some countries, acquired critical importance, became a trigger for the revision and shift of the main emphases in the formation of the innovative mechanisms of state economic policy implementation aimed at ensuring the national economic stability. The volume of shadow financial flows plays an important role in these processes, in the structure of which there is a constant increase in the share of shadow operations with the participation of financial intermediaries (Boyko, 2011;Gaspareniene et al, 2017;Kremen et al, 2018;Lyeonov et al, 2021;Affandi and Malik, 2020).…”
mentioning
confidence: 99%
“…The problems of the rapid economic crisis aggravation in Ukraine and the world, the shortage of financial resources, the bankruptcy of a significant number of companies, which only worsened in the conditions of the COVID-19 pandemic, and in some countries, acquired critical importance, became a trigger for the revision and shift of the main emphases in the formation of the innovative mechanisms of state economic policy implementation aimed at ensuring the national economic stability. The volume of shadow financial flows plays an important role in these processes, in the structure of which there is a constant increase in the share of shadow operations with the participation of financial intermediaries (Boyko, 2011;Gaspareniene et al, 2017;Kremen et al, 2018;Lyeonov et al, 2021;Affandi and Malik, 2020).…”
mentioning
confidence: 99%
“…Besides, one of the scientific papers (Gatsi, 2020) examines the impact of international remittances on the level of financial inclusion of Ghana's population. It was found that the intensification of the flow of international remittances increases the number of open bank http://mmi.fem.sumdu.edu.ua/en accounts and the quality of banking services (Leonov et al, 2018;Lyeonov et al, 2020). Budget management's effectiveness as the basis of public financial management is widely disclosed in the world scientific community.…”
mentioning
confidence: 99%